Harnessing Zero-Tillage: Enhancing Garlic Growth and Yield via Rice Stubble Planting and Mulch Optimization in Far-Western Nepal - Bhatta, Bhawana; Giri, Hom Nath (Agronomy Journal of Nepal, 2025)
Garlic planted in Nepal suffers from low yield due to inadequate soil moisture, delayed planting leading to high temperature exposure, and soil degradation from conventional tillage methods, especially in the areas where it is cultivated as a short winter crop after harvesting the rice. Field research was conducted to evaluate the effect of various tillage and mulching practices in local garlic variety grown after harvesting of rice in Kailali district of Nepal. The field study was conducted at Godawari, Kailali, from November 2021 to April 2022, and evaluated the effects of tillage and mulching on garlic growth and yield using a split-plot design with four replications. The main plot comprised two tillage methods, viz., zero tillage and conventional tillage, whereas the subplot consisted of five mulching practices, i.e., rice straw, rice husk, sawdust, sugarcane trash, and dried leaves. Zero tillage showed significantly higher (p